Searches for pair-produced multijet resonances using data scouting in proton-proton collisions at sqrt[s]=13 TeV - Hayrapetyan,A; Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Hussain,PS; Jeitler,M; Krammer,N; Li,A; et al. (Physical Review Letters, 2024)
Searches for pair-produced multijet signatures using data corresponding to an integrated luminosity of 128  fb−1 of proton-proton collisions at √=13  TeV are presented. A data scouting technique is employed to record events with low jet scalar transverse momentum sum values. The electroweak production of particles predicted in -parity violating supersymmetric models is probed for the first time with fully hadronic final states. This is the first search for prompt hadronically decaying mass-degenerate higgsinos, and extends current exclusions on -parity violating top squarks and gluinos.